Effects of Web-Based Mindfulness-Based Interventions on Anxiety, Depression, and Stress Among Frontline Health Care Workers During the COVID-19 Pandemic: Systematic Review and Meta-Analysis - Jia-ming Yang; Hua Ye; Yi Long; Qiang Zhu; Hui Huang; Yan-biao Zhong; Yun Luo; Lei Yang; Mao-yuan Wang (JMIR Publications, 2023)
BackgroundSince 2019, the COVID-19 outbreak has spread around the world, and health care workers, as frontline workers, have faced tremendous psychological stress. ObjectiveThe purpose of this study is to explore whether web-based mindfulness-based interventions continue to have a positive impact on anxiety, depression, and stress among health care workers during the COVID-19 pandemic. MethodsThe inclusion criteria were as follows: (1) participants were frontline health care workers during the COVID-19 pandemic; (2) the experimental group was a web-based mindfulness-based intervention; (3) the control group used either general psychological intervention or no intervention; (4) outcome indicators included scales to assess anxiety, depression, and stress; and (5) the study type was a randomized controlled study. Studies that did not meet the above requirements were excluded. We searched 9 databases, including Web of Science, Embase, PubMed, Cochrane Library, Scopus, ScienceDirect, SinoMed, China National Knowledge Infrastructure (CNKI), and Wanfang Database, for randomized controlled studies on the effects of web-based mindfulness-based interventions on common mental disorder symptoms among health care workers from January 1, 2020, to October 20, 2022. The methodological quality of the included studies was assessed using the Physiotherapy Evidence Database scale. The Cochrane risk of bias tool was used to assess the risk of bias. Subgroup analysis was used to look for sources of heterogeneity and to explore whether the results were the same for subgroups under different conditions. Sensitivity analysis was used to verify the stability of the pooled results. ResultsA total of 10 randomized controlled studies with 1311 participants were included. The results showed that web-based mindfulness-based interventions were effective in reducing the symptoms of anxiety (standard mean difference [SMD]=-0.63, 95% CI -0.96 to -0.31, P<.001, I2=87%), depression (SMD=-0.52, 95% CI -0.77 to -0.26, P<.001, I2=75%), and stress (SMD=-0.20, 95% CI -0.35 to -0.05, P=.01, I2=58%) among health care workers during the COVID-19 pandemic, but with wide CIs and high heterogeneity. ConclusionsWeb-based mindfulness-based interventions may be effective in reducing the symptoms of anxiety, depression, and stress among frontline health care workers during the COVID-19 pandemic. However, this effect is relatively mild and needs to be further explored by better studies in the future. Trial RegistrationPROSPERO CRD42022343727; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=343727